Strengths and Weaknesses of Collaborative Writing and Peer Feedback in an EFL Intensive Reading and Writing Coursework - Sakhi Herwiana (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
The advantages of collaborative writing and peer feedback have contributed to give significant effect to the writing ability of L1 (first language) learners, L2 (second language) learners, and FL (foreign language) learners. The objective of this study was to find out the strengths and weaknesses of collaborative writing and peer feedback in an EFL intensive reading and writing coursework classroom especially in English education department students of Hasyim Asy’ari University. This study used a qualitative method where the data were described qualitatively. As this study used a qualitative approach, therefore observation and interview were used as instruments to collect the data. The result showed that collaborative writing and peer feedback strategies were not easy to be implemented in an EFL classroom. There were some strengths and weaknesses found during the observation. The strengths of these strategies showed that students could share ideas, improve grammar and vocabulary, make students more active, have good cooperation among peers, build self-confidence and make students happy. However, the strategies may not give any significant effect on the students’ cognitive ability in writing skills if most of the students have the low ability in mastering English. In addition, a smart student would prefer to write individually than in collaborative writing.